Sodium in feline nutrition. Issue 3 (23rd August 2016) - Nguyen, P.; Reynolds, B.; Zentek, J.; Paßlack, N.; Leray, V.
Summary: High sodium levels in cat food have been controversial for a long time. Nonetheless, high sodium levels are used to enhance water intake and urine volume, with the main objective of reducing the risk of urolithiasis. This article is a review of current evidence of the putative risks and benefits of high dietary sodium levels. Its secondary aim is to report a possible safe upper limit (SUL) for sodium intake. The first part of the manuscript is dedicated to sodium physiology, with a focus on the mechanisms of sodium homeostasis. In this respect, there is only few information regarding possible interactions with other minerals. Next, the authors address how sodium intake affects sodium balance; knowledge of these effects is critical to establish recommendations for sodium feed content. The authors then review the consequences of changes in sodium intake on feline health, including urolithiasis, blood pressure changes, cardiovascular alterations and kidney disease. According to recent, long‐term studies, there is no evidence of any deleterious effect of dietary sodium levels as high as 740 mg/MJ metabolizable energy, which can therefore be considered the SUL based on current knowledge.